Contactless photomagnetoelectric investigations of 2D semiconductors - Nowak, Marian; Jesionek, Marcin; Solecka, Barbara; Szperlich, Piotr; Duka, Piotr; Starczewska, Anna (Beilstein Journal of Nanotechnology, 2018)
Background: Applications of two-dimensional (2D) materials in electronic devices require the development of appropriate measuring methods for determining their typical semiconductor parameters, i.e., mobility and carrier lifetime. Among these methods, contactless techniques and mobility extraction methods based on field-effect measurements are of great importance.Results: Here we show a contactless method for determining these parameters in 2D semiconductors that is based on the photomagnetoelectric (PME) effect (also known as the photoelectromagnetic effect). We present calculated dependences of the PME magnetic moment, evoked in 2D Corbino configuration, on the magnetic field as well as on the intensity and spatial distribution of illumination. The theoretical predictions agree with the results of the contactless investigations performed on non-suspended single-layer graphene. We use the contactless PME method for determining the dependence of carrier mobility on the concentration of electrons and holes induced by a back-gate voltage.Conclusion: The presented contactless PME method, used in Corbino geometry, is complementary to the mobility extraction methods based on field-effect measurements. It can be used for determining the mobility and diffusion length of carriers in different 2D materials.
Keywords: carrier mobility; contactless investigations; graphene; photomagnetoelectric effect; 2D materials